Day 1 Tue, March 23, 2021 2021
DOI: 10.2523/iptc-21818-ms
|View full text |Cite
|
Sign up to set email alerts
|

Material Selection and Corrosion Rate Analysis for CO2 Injection Well: A Case Study of K1 Field CO2 Sequestration Project

Abstract: The CO2 sequestration project is becoming increasingly attractive due to tax exemption benefits and as an initiative to reduce the global warming effect (D'Alesio, P., Poloni, R., Valente, P., & Magarini, P. A.2010). One of the major challenges in CO2 sequestration project is to ensure that the injection well integrity is intact throughout the well operating life. CO2 gas leakage to the surface or sea is unacceptable. Therefore, the considerations of using exotic/premium tubing materials are usually consid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 5 publications
0
2
0
Order By: Relevance
“…CO 2 injection has emerged as an important method for enhancing oil recovery. Experimental tests and simulations have been undertaken to evaluate the improvement of recovery by CO 2 injections. In the context of the shale oil and gas field, CO 2 can be used to stimulate the development of shale oil and gas via adsorption and replacement processes. Researchers have carried out experimental and dynamic simulation studies on CO 2 -enhanced recovery in shale formations. , These experimental analysis included mechanical characterization, modification in pore-throat structures, alterations in mineral content, changes in adsorption–desorption, and variations in pore and permeability levels. Existing experimental studies conducted under conventional temperature and pressure settings have found that the interaction between CO 2 and reservoir rocks considerably influences the rock properties.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…CO 2 injection has emerged as an important method for enhancing oil recovery. Experimental tests and simulations have been undertaken to evaluate the improvement of recovery by CO 2 injections. In the context of the shale oil and gas field, CO 2 can be used to stimulate the development of shale oil and gas via adsorption and replacement processes. Researchers have carried out experimental and dynamic simulation studies on CO 2 -enhanced recovery in shale formations. , These experimental analysis included mechanical characterization, modification in pore-throat structures, alterations in mineral content, changes in adsorption–desorption, and variations in pore and permeability levels. Existing experimental studies conducted under conventional temperature and pressure settings have found that the interaction between CO 2 and reservoir rocks considerably influences the rock properties.…”
Section: Introductionmentioning
confidence: 99%
“…Experimental tests and simulations have been undertaken to evaluate the improvement of recovery by CO 2 injections. 1 3 In the context of the shale oil and gas field, CO 2 can be used to stimulate the development of shale oil and gas via adsorption and replacement processes. Researchers have carried out experimental and dynamic simulation studies on CO 2 -enhanced recovery in shale formations.…”
Section: Introductionmentioning
confidence: 99%